Math, asked by KUKKALARAVISESHU, 1 year ago

verfiy that
p³+q³+r³-3pqr=(p+q+r)(p²+q²+r²-pq-qr-rp)​

Answers

Answered by vinnmathy
0

Answer:

solve earning subtraction method 10x+2y=4 15x-5y=-2​ explanation:

Answered by Akshithayadav
3

Answer:

Given:-)

→ p + q + r = 6.

→ pq + qr + rp = 5.

To Find :-)

→ p³ + q³ + r³ - 3pqr.

▶ We have,

=> p + q + r = 6.

[ Squaring both side ]

=> ( p + q + r ) ² = 6².

=> p² + q² + r² + 2 ( pq + qr + rp ) = 36.

=> p² + q² + r² + 2 ( 5 ) = 36.

=> p² + q² + r² + 10 = 36.

=> p² + q² + r² = 36 - 10.

=> p² + q² + r² = 26.

▶Now,

=> p³ + q³ + r³ - 3pqr = ( p + q + r ) ( p² + q² + r² - ( pq + qr + rp ) ).

= ( 6 ) ( 26 - (5) ).

= 6 × 21.

= 126.

✔✔Hence, it is solved ✅✅.

Similar questions